2018
DOI: 10.1088/1361-6528/aabf10
|View full text |Cite
|
Sign up to set email alerts
|

Suggested design of gold-nanoobjects-based terahertz radiation source for biomedical research

Abstract: Gold nanoparticles (GNPs) may serve as devices to emit electromagnetic radiation in the terahertz (THz) range, whereby the energy is delivered by radio frequency or microwave photons which will not by themselves induce transitions between sparse confinement-shaped electron levels of a GNP, but may borrow the energy from longitudinal acoustic (LA) phonons to overcome the confinement gap. Upon excitation, the Fermi electron cannot relax otherwise than via emitting a THz photon, the other relaxation channels bein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Further on, in Ref. 24 we have shown that gold nanorhombicuboctahedra could be used as emitters of radiation at "soft" (two-phonon difference frequency) 0.54 THz and at "hard" (summary frequency) 8.7 THz. The 0.5 THz emission is important for the THz imaging of human skin cancer, due to maximal contrast it yields between the cancer and the normal tissue, in the context of findings of Wallace and Pickwell 19,20 .…”
Section: General Idea and Setup Of The Terahertz-to-infrared Convmentioning
confidence: 96%
“…Further on, in Ref. 24 we have shown that gold nanorhombicuboctahedra could be used as emitters of radiation at "soft" (two-phonon difference frequency) 0.54 THz and at "hard" (summary frequency) 8.7 THz. The 0.5 THz emission is important for the THz imaging of human skin cancer, due to maximal contrast it yields between the cancer and the normal tissue, in the context of findings of Wallace and Pickwell 19,20 .…”
Section: General Idea and Setup Of The Terahertz-to-infrared Convmentioning
confidence: 96%
“…2 in Ref. 25 parametrised the experimental Γ − X dispersion relation for bulk gold and elaborated on the matching conditions between the energy of absorbed/released phonons, ω(q 1 )− ω(q 2 ), and the quantisation step on the electron excitation.…”
Section: A General Considerationsmentioning
confidence: 99%
“…Such an analysis has been done in Ref. 25, albeit with compact GNPs (not elongated GNBs) in mind. The discussion around Fig.…”
Section: A General Considerationsmentioning
confidence: 99%
“…In Ref. [10] it was shown that gold nanorhombicuboctahedra could be used as emitters of radiation at 0.54 and at 8.7 THz, important for the THz imaging of human skin cancer, in the context of findings of Ref. [11,12] and possible impact on the improvement of spatial resolution.…”
mentioning
confidence: 99%